Old Meany Hall, University of Washington, probably between 1908 and 1952 - Todd, Calvin F. (1908)
Meany Hall was built in 1908 to serve as the auditorium for the Alaska-Yukon-Pacific Exposition. It was demolished in 1965 after suffering extensive damage in an earthquake. Unnumbered Todd, Filed in: Box 4